Fostering Futures: Integrating Technology and Awaress For Community Mental Wellbeing - Rifat N Kusumaningtyas; Rina Kusumaratna; Dian Kusuma (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2026)
Mental health issues affect over a quarter of the global population, contributing significantly to the global health burden. Tackling these challenges requires effective prevention, care management, and community-driven strategies to reduce stigma and promote mental well-being. This study explores how digital innovation—specifically the integration of the e-Self Reporting Questionnaire (e-SRQ-20)—can foster mental health awareness and encourage proactive care-seeking behaviors. Conducted from October to December 2022, a community-based cross-sectional study involved 135 participants across 11 neighborhood units in the PU Health Centre, South Jakarta. Using purposive sampling, participants completed the e-SRQ-20 with support from medical doctors and health volunteers. Findings showed that 61% were aged 35–55, 84% were women, and 64% were housewives, with common symptoms including fatigue, somatic complaints, depression, and anxiety. Yet, only 31.6% of those scoring above the threshold sought further care—highlighting critical gaps in service access. These results underscore the need to empower individuals, families, and communities through awareness and inclusive digital tools. Integrating electronic screening into primary care offers a promising pathway to make mental health services more accessible, affordable, and acceptable